2019
DOI: 10.1186/s40066-018-0249-2
|View full text |Cite
|
Sign up to set email alerts
|

Early growth trend and performance of three Ethiopian goat ecotypes under smallholder management systems

Abstract: Objective: The present study aimed to evaluate the early growth performance of three Ethiopian goat populations (Bati, Borana and Short-eared Somali) from birth to 180 days and the influence of non-genetic factors such as sex, gemellarity and parity as well as goat ecotype on body weight (BW) and average daily weight gain (ADWG). Methods:A total of 350 heads of breeding does (113 Bati, 137 Borana and 100 Short-eared Somali) were used, and the kids were monitored for 1 year at birth, 30, 90 and 180 days of age.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
5
4
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 10 publications
8
5
4
3
Order By: Relevance
“…In most animal species, average weight gain per day (WG) is used to evaluate growth rates and animals with higher growth rates can gain weight in a shorter period with a low amount of production inputs. The decreasing trend of weight gain when the age increases in this study concurs with Gatew et al. (2019) and Deribe and Taye (2013) .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In most animal species, average weight gain per day (WG) is used to evaluate growth rates and animals with higher growth rates can gain weight in a shorter period with a low amount of production inputs. The decreasing trend of weight gain when the age increases in this study concurs with Gatew et al. (2019) and Deribe and Taye (2013) .…”
Section: Discussionsupporting
confidence: 92%
“…In most animal species, average weight gain per day (WG) is used to evaluate growth rates and animals with higher growth rates can gain weight in a shorter period with a low amount of production inputs. The decreasing trend of weight gain when the age increases in this study concurs with Gatew et al (2019) and Deribe and Taye (2013). This is not surprising, because, besides genetic potential and other environmental factors, pre-weaning weight gain of kids is closely associated with the nutritional status of the dam, mothering ability and milk production potential of the dam.…”
Section: Weight Gainsupporting
confidence: 92%
See 1 more Smart Citation
“…Several studies have shown the significant effects of PA on the early growth performance of kids from different goat breeds (Abergelle goats [ 24 ] and Ethiopian goats [ 25 ]). A significant association between the parity order and the ADG was revealed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…For that reason, exhaustive characterization programs helps to provide a better understanding of the potential of indigenous goat populations in Tanzania and allow for sustainable improvement and utilization. (Nguluma et al, 2016;Msemwa & Mbaga, 2018), for SEA goats in Rwanda (Manzi et al, 2011), for Tswana goats in Botswana (Katogole et al, 1996;Monau et al, 2018), for Beni arrous goats in Morocco (Hilal et al, 2014) and for indigenous goat populations from various ecological zones of Ethiopia (Muluneh et al, 2016;Gatew et al, 2017;Gebreyowhens & Kumar, 2017;Tilahun et al, 2019). Appearance of beards is influenced by sex (sexual dimorphism) and does displaying the feature might have more secretion of androgens, a male hormone (Adedeji et al, 2006;Hilal et al, 2014).…”
Section: Variation In Live Measurement Traitsmentioning
confidence: 99%